2001
DOI: 10.1002/jid.814
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of drudgery in agricultural and animal husbandry operations: a gender analysis from Haryana State, India

Abstract: The paper examines the involvement and drudgery profile of rural women and men in agricultural and animal husbandry activities in India. The activities assigned to men were those which were considered to demand greater physical power, skill and performance. The activities assigned to women were considered to demand less physical power, lower skill and more time. They were also monotonous in their nature and low paid. The implications of the study indicate a need to match technological and innovative solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This shift in the location may have important labor and gender implications for technology development and extension. It may suggest, for example, as illustrated in recent reviews (Doss, 2001;Thakur et al, 2001), that technology is not gender neutral and may be a key factor explaining women's inability to benefit from improved technologies. Begum (1985) has shown that in Asian rice farming systems, the total of labor time required to process rice (an arena dominated by Asian women) is almost equal to that required to produce the rice from seed to the point of harvest (1985:224).…”
Section: Downloaded By [Temple University Libraries] At 03:55 19 Novementioning
confidence: 94%
See 1 more Smart Citation
“…This shift in the location may have important labor and gender implications for technology development and extension. It may suggest, for example, as illustrated in recent reviews (Doss, 2001;Thakur et al, 2001), that technology is not gender neutral and may be a key factor explaining women's inability to benefit from improved technologies. Begum (1985) has shown that in Asian rice farming systems, the total of labor time required to process rice (an arena dominated by Asian women) is almost equal to that required to produce the rice from seed to the point of harvest (1985:224).…”
Section: Downloaded By [Temple University Libraries] At 03:55 19 Novementioning
confidence: 94%
“…Yet overarching socially inscribed norms define women's responsibilities as subordinate to what men do (Thakur, Varma and Goldey, 2001;Doss, 2001;Kabeer and Van Anh, 2001;Thomas Slayter and Sodikoff, 2001). When gendered relations of production are ignored in technology development and innovation, women often face serious dis-articulations in agricultural workloads and access to resources, which support their caregiving responsibilities (Beneria, and Feldman, 1992;Saito, 1994).…”
Section: Gender and Agricultural Technology Developmentmentioning
confidence: 96%
“…Traditionally, decision making and managerial roles have been either denied or constrained for women in the animal husbandry sector in India due to the paternalistic bias of Indian society [32]. Gender inequalities favoring males exist in access to information, as well as ownership of land and livestock in Indian society [33]. The women are mostly confined to household work, including tending to livestock at home whereas the men work outside the homes to earn a stable income.…”
Section: Human and Cattle Demographicsmentioning
confidence: 99%